Role of Nitric Oxide in Neuronal Damages in Critical Conditions - A. V. Kiseleva; Yu. A. Churlyaev; Ye. V. Grigoryev (Общая реаниматология, 2009)
The presented review of literature covers the current notions of the role of nitric oxide and its metabolism in the development of encephalopathies in critically ill patients. The mechanisms of nitric oxide involvement in neurotoxicity, neuronal induction of apoptosis, and the types of nitric oxide involvement in the development of brain ischemia, focal cerebral damage in severe brain injury are described. A concise review of the experimentally founded therapy options aimed at correcting nitric oxide-induced neuronal damage (modulation of nitric oxide synthesis, antioxidants) is given. Key words: brain ischemia, brain traumatic injuries, nitric oxide synthase variants, neurotoxicity, apoptosis, correction modes.